Dual-mode dual-band bandpass filter using a single slotted circular patch resonator - Zhang, Runqi (2013)
A single slotted circular patch resonator is proposed in this letter to design a novel dual-mode dual-band bandpass filter. Four identical arc-oriented slots are first symmetrically etched into the circular patch resonator to move the TM01-like mode to a lower frequency. Together with the TM21-like mode, these two modes make up the second passband of the proposed filter. A pair of radial-oriented slots is then etched into the edge of the circular patch to split a pair of TM11-like degenerate modes, which forms the first dual-mode passband. Two high-impedance transmission lines are connected to the proposed resonator at a 90° angle to properly excite the four resonant modes described above. Finally, a filter with input/output cross coupling is designed, fabricated and tested to demonstrate the dual-mode dual-band filtering performance, which exhibits a sharp out-of-band rejection skirt and good rejection between the dual passbands.